1901 Ind. Acts 206, Public Comfort and Health, § 4077 - (:unkn) unknown (General Publisher, 1901)
Allowed the cities with populations of more than thirty thousand and less than thirty six and a half thousand in population to regulate the storage of gun powder, tar, pitch, resin, coal oil, benzene, turpentine, hemp, cotton, nitroglycerine, dynamite, giant powder, petroleum, gasoline, or gas, or other explosive or combustible material which may seem dangeorus
--
Keywords: GUN POWDER STORAGE